A composite material based on graphene foam and a method for preparing the same

CN122974376APending Publication Date: 2026-10-27CHONGQING DONGPAN CARBON MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611173292.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明针对现有三维石墨烯基电催化材料制备工艺复杂、结构稳定性差、活性组分易团聚、氮掺杂效率低、难以工业化放大等缺陷,核心目的在于:一是提供一种工艺可控、成本低廉、适于工业化放大生产的基于石墨烯泡沫体的复合材料的制备方法,通过两步气相原位氮掺杂与碳纳米管原位生长工艺,同步实现载体增韧与高效氮掺杂;二是提供由上述制备方法制得的结构稳定、活性位点丰富、ORR/OER双功能催化性能优异的复合材料;三是实现该复合材料在新能源电催化领域的高效实用化应用

Benefits of technology

[0014]本发明通过制备工艺的体系创新,实现了多重技术突破,具备显著的技术效益、经济效益与产业化应用效益,具体如下:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974376A_ABST
    Figure CN122974376A_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite material based on graphene foam and preparation method thereof, belong to new energy nanometer material technical field.The application is prepared in situ nitrogen-doped three-dimensional graphene foam by once CVD in combination with gas phase in-situ nitrogen doping with foam nickel as template;After loading carbon nanotube growth catalyst, it is realized in-situ covalent growth of nitrogen-doped carbon nanotube on the surface of skeleton by secondary CVD in combination with gas phase in-situ nitrogen doping, and modified carrier is obtained by etching;Again, CoFe2O4 bimetallic nanoparticles are loaded by vacuum impregnation, and the composite material of the application is prepared by combining organic nitrogen source in-situ polymerization-high temperature calcination process.The composite material obtained by the application has stable structure, rich active sites, excellent dual-function catalytic performance for oxygen reduction and oxygen evolution, and can be directly used as a self-supporting electrocatalytic electrode without adding binder and additional current collector, and can be widely used in fuel cells, metal-air batteries, water electrolysis hydrogen production and other new energy devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy nanomaterials technology, specifically to a composite material based on graphene foam and its preparation method. Background Technology

[0002] Driven by the "dual carbon" goal, clean and efficient new energy devices such as fuel cells, metal-air batteries, and water electrolysis for hydrogen production have become core technological directions for replacing the traditional fossil energy system. The energy conversion efficiency, cycle life, and core cost of these new energy devices directly depend on the electrocatalytic materials of their cathodes and anodes, especially bifunctional electrocatalysts that can simultaneously drive the oxygen reduction reaction and the oxygen evolution reaction.

[0003] Currently, commercially available electrocatalytic materials are mainly noble metal-based catalysts. Among them, platinum-based (Pt / C) catalysts exhibit excellent catalytic performance for the oxygen reduction reaction, while iridium / ruthenium-based (IrO2 / RuO2) catalysts show outstanding catalytic effects for the oxygen evolution reaction. However, these materials have inherent drawbacks that cannot be overcome: First, noble metals are scarce in the Earth's crust and have extremely high preparation costs, which cannot support the large-scale promotion and application of new energy devices. Second, they have significant single-function catalytic characteristics and cannot simultaneously meet the catalytic requirements of both oxygen reduction and oxygen evolution reactions. Third, they have poor cycle stability and are prone to aggregation, dissolution, and poisoning deactivation during long-term charge-discharge processes, making it difficult to meet the requirements for long-term use of devices.

[0004] To address the shortcomings of noble metal catalysts, non-noble metal transition metal oxide / carbon-based composite electrocatalytic materials have become a core research focus in the industry. Among them, three-dimensional graphene foam, with its advantages of high electrical conductivity, three-dimensional interconnected porous structure, and large specific surface area, is an ideal carrier for loading non-noble metal active components. However, its preparation and application still face many technical bottlenecks.

[0005] 1. Pure three-dimensional graphene foam has poor mechanical stability. Existing modification and preparation processes mostly adopt the method of physical mixing of carbon nanotubes and subsequent impregnation and loading, which has problems such as weak bonding between carbon nanotubes and graphene foam, easy detachment, and uneven dispersion. It cannot fundamentally solve the defect of easy structural collapse. 2. Graphene foam framework has a smooth surface and strong chemical inertness, making it difficult to uniformly load non-noble metal nanoparticles. Existing nitrogen doping modification processes are cumbersome, have uneven doping, poor controllability of nitrogen active configuration, and low overall nitrogen content. They cannot form effective synergy with transition metal active sites, making it difficult to construct high-density MNC highly active catalytic sites. 3. Existing graphene-based electrocatalysts are mostly powder materials, with complex preparation processes and poor batch stability. Electrode preparation requires the addition of binders and additional current collectors, which will cover a large number of active sites, increase the internal resistance of the electrode, and severely reduce the reaction efficiency, making it difficult to achieve large-scale industrial production. 4. The bifunctional catalytic synergistic effect of single-metal transition metal oxide catalysts is weak. Existing bimetallic catalyst preparation processes cannot achieve confined anchoring of active components. They are prone to loss and aggregation during long-term reaction, and their cycle stability is difficult to meet industrialization requirements. In summary, the existing technology lacks a method for preparing non-precious metal bifunctional electrocatalytic materials that has high process integration, controllable parameters, is suitable for industrial production, and can simultaneously achieve structural toughening, efficient nitrogen doping, and confinement of active components. This has become one of the core technological bottlenecks restricting the large-scale promotion of new energy devices. Summary of the Invention

[0006] This invention addresses the shortcomings of existing three-dimensional graphene-based electrocatalytic materials, such as complex preparation processes, poor structural stability, easy aggregation of active components, low nitrogen doping efficiency, and difficulty in industrial scale-up. The core objectives are: first, to provide a method for preparing graphene foam-based composite materials that is process-controllable, low-cost, and suitable for industrial-scale production, achieving simultaneous support toughening and efficient nitrogen doping through a two-step gas-phase in-situ nitrogen doping and carbon nanotube in-situ growth process; second, to provide a composite material with stable structure, abundant active sites, and excellent ORR / OER bifunctional catalytic performance prepared by the above method; and third, to realize the efficient and practical application of this composite material in the field of new energy electrocatalysis.

[0007] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows: First, this invention provides a method for preparing a composite material based on graphene foam, comprising the following steps: (1) Using chemical vapor deposition, with nickel foam as a template, carbon source and gaseous nitrogen source are introduced. Through a single chemical vapor deposition (CVD) combined with gaseous in-situ nitrogen doping process, in-situ nitrogen-doped three-dimensional graphene foam is grown on the surface of nickel foam to obtain nickel foam-loaded in-situ nitrogen-doped three-dimensional graphene foam. (2) Carbon nanotube growth catalyst is loaded on the surface of the in-situ nitrogen-doped three-dimensional graphene foam supported by nickel foam obtained in step (1). After secondary CVD combined with gas phase in-situ nitrogen doping process, nitrogen-doped carbon nanotubes are covalently grown on the surface of the in-situ nitrogen-doped three-dimensional graphene foam skeleton supported by nickel foam. After etching to remove the nickel foam template, a graphene foam carrier modified with nitrogen-doped carbon nanotubes is obtained. (3) The CoFe2O4 bimetallic oxide nanoparticle dispersion was loaded onto the surface of the nitrogen-doped carbon nanotube modified graphene foam carrier obtained in step (2), dried, and then impregnated in an organic nitrogen source doping solution. The precursor was obtained by in-situ polymerization at room temperature. (4) The precursor obtained in step (3) is calcined in an inert atmosphere to obtain the composite material based on graphene foam.

[0008] Furthermore, in step (1), the specific steps of the chemical vapor deposition method are as follows: The nickel foam was placed in a CVD tube furnace and heated to 960-990 ℃ at a heating rate of 8-12 ℃ / min under argon protection. Hydrogen was then introduced and reduced at a constant temperature for 25-40 min at a hydrogen flow rate of 20-60 sccm. Then a mixture of carbon source, hydrogen and gaseous nitrogen source was introduced, with a flow rate ratio of carbon source to hydrogen of 1:(12-18) and a flow rate ratio of gaseous nitrogen source to carbon source of 1:(5-20), and the mixture was grown at a constant temperature for 12-18 min. After growth, the temperature was lowered to room temperature under a protective atmosphere of mixed argon and hydrogen to obtain in-situ nitrogen-doped three-dimensional graphene foam supported on nickel foam.

[0009] Further, in step (2), the carbon nanotube growth catalyst is one or more of iron salts, cobalt salts, nickel salts, iron oxide, cobalt oxide, iron(II,III) oxide, or nickel oxide, and the loading method is impregnation, spin coating, or sputtering, with a catalyst loading of 0.1-0.5 mg / cm³. 2 ; The specific steps of the secondary CVD combined with gas phase in-situ nitrogen doping process are as follows: under argon protection, the temperature is raised to 850-950℃, and a mixed gas of carbon source, hydrogen and gas phase nitrogen source is introduced. The flow rate ratio of carbon source to hydrogen is 1:(10-15), and the flow rate ratio of gas phase nitrogen source to carbon source is 1:(3-15). The growth is carried out at a constant temperature for 15-30 min. The etching was performed using a 1.0-2.5 mol / L FeCl3 / HCl mixed etching solution for 18-30 h. The carbon source is one or more of methane, ethylene, propylene, ethane, or propane; the gaseous nitrogen source is one or more of ammonia, urea vapor, or melamine vapor.

[0010] Further, in step (3), the concentration of the CoFe2O4 bimetallic oxide nanoparticle dispersion is 0.8-4.5 mg / mL, the loading method is impregnation, the impregnation time is 2-4 h, and the impregnation and drying are repeated 2-4 times; the solute of the organic nitrogen source doping solution is one or more of dopamine hydrochloride, dopamine, melamine, pyrrole, aniline, urea or chitosan, the concentration of organic nitrogen source in the organic nitrogen source doping solution is 1.2-4.8 mg / mL, the impregnation polymerization reaction time is 8-14 h, and the reaction environment is room temperature and protected from light.

[0011] Further, in step (4), the calcination process is as follows: under a high-purity nitrogen or argon atmosphere, the temperature is raised to 580-630 ℃ at a heating rate of 3-6℃ / min, and calcined at a constant temperature for 1.5-2.5 h. After calcination, the temperature is lowered to room temperature under an inert atmosphere.

[0012] Secondly, the graphene foam-based composite material prepared by the above method uses in-situ nitrogen-doped three-dimensional graphene foam as the matrix framework, and nitrogen-doped carbon nanotubes are covalently grown in-situ on the surface of the in-situ nitrogen-doped three-dimensional graphene foam framework to form a nitrogen-doped carbon nanotube-modified graphene foam carrier; the surface of the nitrogen-doped carbon nanotube-modified graphene foam carrier is in-situ coated with an organic nitrogen source-derived nitrogen-doped carbon layer, and CoFe2O4 bimetallic oxide nanoparticles are uniformly anchored in the organic nitrogen source-derived nitrogen-doped carbon layer to form a hierarchical integrated structure.

[0013] The core structural features of this composite material, which serve as a unique technological advantage of its preparation method, are as follows: the nitrogen-doped carbon nanotubes are single-walled or multi-walled carbon nanotubes with a diameter of 10-100 nm and a length of 5-50 μm; the in-situ nitrogen-doped three-dimensional graphene foam inherits the three-dimensional interconnected porous structure of the nickel foam template, with a pore size of 80-350 μm, a porosity of 98.5%-99.5%, and a nitrogen doping atomic percentage of 0.5-2.0 at.%. The CoFe2O4 bimetallic oxide nanoparticles have a particle size of 80-450 nm and are spatially confined and anchored by the nitrogen-doped carbon layer; the thickness of the nitrogen-doped carbon layer derived from the organic nitrogen source is 2-12 nm, and the nitrogen doping atomic percentage is 1.2-4.5 at.%.

[0014] This invention achieves multiple technological breakthroughs through systemic innovation in the preparation process, resulting in significant technical, economic, and industrial application benefits, as detailed below: (1) This invention utilizes a two-step chemical vapor deposition integrated preparation process to sequentially complete the growth of graphene foam and the in-situ growth of carbon nanotubes on the same template. The process steps are highly consistent and the batch stability is high. The secondary CVD in-situ growth process realizes the covalent bonding between nitrogen-doped carbon nanotubes and the graphene foam framework, constructing a hierarchical three-dimensional porous framework with cross-linked and toughened carbon nanotubes. This process not only fully preserves the interconnected porous ion / electron transport channels of the three-dimensional graphene foam, but also fundamentally solves the industry pain points of easy detachment and uneven dispersion of carbon nanotubes in traditional physical loading processes. At the same time, the in-situ grown carbon nanotubes significantly increase the specific surface area of ​​the support, providing sufficient sites for the uniform anchoring of catalytic active sites and significantly optimizing the mass transfer and electron transport efficiency of the electrocatalytic reaction.

[0015] (2) The present invention adopts a three-stage nitrogen doping preparation process of two gas-phase in-situ nitrogen doping combined with organic nitrogen source post-doping. Nitrogen doping is achieved simultaneously in the graphene foam matrix growth, carbon nanotube growth and subsequent carbonization process. No additional post-doping treatment steps are required, which greatly improves the overall nitrogen content and doping uniformity of the material. The uniformly doped nitrogen element forms a strong electronic interaction with Co and Fe bimetals, constructing a high-density Co-NC and Fe-NC highly active catalytic sites. At the same time, a strong synergistic effect is formed between Co and Fe bimetals, which can simultaneously optimize the reaction energy barrier of oxygen reduction and oxygen evolution reaction, and realize the simultaneous improvement of bifunctional electrocatalytic performance.

[0016] (3) This invention uses a room-temperature in-situ polymerization-high-temperature calcination process to form a uniformly coated nitrogen-doped carbon layer on the surface of the support, thereby achieving spatial confinement and anchoring of CoFe2O4 bimetallic oxide nanoparticles. The process conditions are mild and the operation is simple. The physical confinement effect of the nitrogen-doped carbon layer can effectively prevent the aggregation, shedding and dissolution of metal nanoparticles during preparation and long-term reaction, ensuring the long-term stable exposure of active sites. At the same time, the nitrogen-doped carbon layer acts as a conductive bridge, further enhancing the interfacial electron transport efficiency between the active component and the support, and improving the catalytic reaction kinetics.

[0017] (4) The preparation process of the present invention expands the range of carbon sources from single methane to C1-C4 low carbon hydrocarbons. The process parameter window is wide and highly controllable, which can realize the precise control of material structure and performance. The whole process does not require extreme reaction conditions and expensive equipment. The raw materials are all non-precious metal systems. The carbon source, nitrogen source and catalyst are widely available and inexpensive. No toxic and harmful by-products are generated. It is green and environmentally friendly and fully adaptable to large-scale industrial production.

[0018] (5) The composite material prepared by the present invention is a complete three-dimensional self-supporting integral block structure, which can be directly cut into working electrodes of fixed size. No binder needs to be added during the electrode preparation process, and no additional current collector is required. This completely solves the industry pain point of traditional powder catalysts covering active sites and increasing electrode internal resistance, effectively reducing electrode preparation cost, and significantly improving electrocatalytic reaction efficiency and cycle stability. It can be widely adapted to a variety of new energy devices and has extremely high industrial application value. Attached Figure Description

[0019] Figure 1 The image shown is a scanning electron microscope image obtained from the test in Example 1. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1 This embodiment is the preferred embodiment of the present invention, and the specific steps for preparing the composite material based on graphene foam are as follows: 1. Nickel foam was placed in the isothermal zone of a horizontal CVD tube furnace, and high-purity argon was introduced as a protective gas. The temperature was increased to 980 ℃ at a heating rate of 10 ℃ / min. After isothermal control, high-purity hydrogen was introduced at a flow rate of 30 sccm, and the reduction was carried out at isothermal control for 30 min. Subsequently, a mixture of methane, hydrogen and ammonia was introduced, with a methane to hydrogen flow rate ratio of 1:15 and an ammonia to methane flow rate ratio of 1:10, and the growth was carried out at isothermal control for 15 min. After the growth was completed, the introduction of methane and ammonia was stopped, and the temperature was reduced to room temperature at a rate of 10 ℃ / min under the protective atmosphere of mixed argon and hydrogen to obtain in-situ nitrogen-doped three-dimensional graphene foam supported on nickel foam.

[0022] 2. Prepare a 0.5 mg / mL anhydrous ethanol dispersion of iron oxide nanoparticles and ultrasonically disperse for 1 h until homogeneous. Spin-coat the dispersion uniformly onto the surface of in-situ nitrogen-doped three-dimensional graphene foam supported on nickel foam at a spin speed of 3500 rpm for 25 s. Repeat the spin-coating process twice. Allow to air dry at room temperature. The catalyst loading is approximately 0.2 mg / cm³. 2 The spin-coated sample was placed again in a CVD tube furnace and heated to 900 °C under argon protection. A mixture of methane, hydrogen, and ammonia was introduced, with a methane to hydrogen flow rate ratio of 1:12 and an ammonia to methane flow rate ratio of 1:8. The sample was grown at this temperature for 20 min to achieve in-situ covalent growth of nitrogen-doped carbon nanotubes on the surface of the graphene foam framework. After cooling to room temperature, the sample was placed in a 1.5 mol / L FeCl3 / HCl mixed etching solution and allowed to stand for 24 h to completely remove the nickel template from the foam. The sample was then repeatedly washed with deionized water and anhydrous ethanol until neutral and freeze-dried under vacuum for 20 h to obtain a nitrogen-doped carbon nanotube-modified graphene foam carrier.

[0023] 3. Prepare a 2.0 mg / mL anhydrous ethanol dispersion of CoFe2O4 nanoparticles and ultrasonically disperse for 1 h until homogeneous. Immerse the nitrogen-doped carbon nanotube-modified graphene foam carrier in the obtained dispersion and vacuum impregnate for 3 h. After removal, vacuum dry at 70 ℃. Repeat the impregnation and drying twice to obtain the CoFe2O4-loaded modified graphene foam carrier. Prepare a Tris-HCl buffer solution with pH=8.0, add dopamine to it, and stir to dissolve to obtain a 2.0 mg / mL nitrogen-doped solution. Immerse the CoFe2O4-loaded modified graphene foam carrier in the nitrogen-doped solution and allow it to stand at room temperature in the dark for 10 h to allow polydopamine to polymerize in situ on the material surface. After removal, wash with deionized water 3 times and vacuum dry at 70 ℃ to obtain the precursor.

[0024] 4. The precursor was placed in a tube furnace and heated to 600 °C at a heating rate of 5 °C / min under a high-purity nitrogen inert atmosphere, and calcined at a constant temperature for 2 h. After calcination, the temperature was lowered to room temperature under nitrogen protection to obtain a graphene foam-based composite material, denoted as CoFe2O4-N-CNT / GF-1.

[0025] The composite material prepared in this embodiment uses in-situ nitrogen-doped three-dimensional graphene foam as the matrix framework, and nitrogen-doped carbon nanotubes are covalently grown in situ on the surface of the in-situ nitrogen-doped three-dimensional graphene foam framework to form a nitrogen-doped carbon nanotube modified graphene foam carrier. The surface of the nitrogen-doped carbon nanotube modified graphene foam carrier is in-situ coated with an organic nitrogen source-derived nitrogen-doped carbon layer, and CoFe2O4 bimetallic oxide nanoparticles are uniformly anchored in the organic nitrogen source-derived nitrogen-doped carbon layer to form a hierarchical integrated structure.

[0026] In this embodiment, the nitrogen-doped carbon nanotubes are mainly multi-walled carbon nanotubes with an average diameter of about 32 nm and an average length of about 22 μm. The in-situ nitrogen-doped three-dimensional graphene foam is a three-dimensional interconnected porous structure with pore sizes mainly distributed in the range of 120-300 μm, a porosity of about 99.2%, and a nitrogen doping atomic percentage of about 1.2 at.

[0027] The CoFe2O4 bimetallic oxide nanoparticles have an average particle size of approximately 180 nm and are spatially confined and anchored by a nitrogen-doped carbon layer. The nitrogen-doped carbon layer derived from the organic nitrogen source has an average thickness of approximately 5 nm and a nitrogen element doping atomic percentage of approximately 3.1 at.%.

[0028] Example 2 In this embodiment, the types of carbon source and gaseous nitrogen source are changed, but the remaining process steps are basically the same as in Example 1, as follows: In step 1, ethylene is used as the carbon source, urea vapor (generated by heating solid urea) is used as the gaseous nitrogen source, the flow ratio of ethylene to hydrogen is 1:14, the flow ratio of urea vapor to ethylene is 1:12, and the other parameters remain unchanged. In step 2, cobalt nitrate was used as the catalyst for carbon nanotube growth, with a loading of approximately 0.3 mg / cm³. 2 The carbon source was ethylene, the flow ratio of ethylene to hydrogen was 1:10, the flow ratio of urea vapor to ethylene was 1:10, and the growth was carried out at a constant temperature for 25 min, with other parameters remaining unchanged. The remaining process steps and parameters are exactly the same as in Example 1, and the composite material is prepared and denoted as CoFe2O4-N-CNT / GF-2.

[0029] The composite material prepared in this embodiment uses in-situ nitrogen-doped three-dimensional graphene foam as the matrix framework, and nitrogen-doped carbon nanotubes are covalently grown in situ on the surface of the in-situ nitrogen-doped three-dimensional graphene foam framework to form a nitrogen-doped carbon nanotube modified graphene foam carrier. The surface of the nitrogen-doped carbon nanotube modified graphene foam carrier is in-situ coated with an organic nitrogen source-derived nitrogen-doped carbon layer, and CoFe2O4 bimetallic oxide nanoparticles are uniformly anchored in the organic nitrogen source-derived nitrogen-doped carbon layer to form a hierarchical integrated structure.

[0030] In this embodiment, the nitrogen-doped carbon nanotubes are mainly multi-walled carbon nanotubes with an average diameter of about 45 nm and an average length of about 30 μm. The in-situ nitrogen-doped three-dimensional graphene foam is a three-dimensional interconnected porous structure with pore sizes mainly distributed in the range of 100-320 μm, a porosity of about 99.0%, and a nitrogen element doping atomic percentage of about 0.9 at.

[0031] The CoFe2O4 bimetallic oxide nanoparticles have an average particle size of about 200 nm and are spatially confined and anchored by a nitrogen-doped carbon layer. The nitrogen-doped carbon layer derived from the organic nitrogen source has an average thickness of about 6 nm and a nitrogen element doping atomic percentage of about 2.8 at.%.

[0032] Example 3 This embodiment adjusts the core process parameters and changes the carbon source; the remaining process steps are basically the same as in Embodiment 1, as detailed below: In step 1, the CVD growth temperature was 960 ℃, the carbon source was propane, the flow ratio of propane to hydrogen was 1:12, the flow ratio of ammonia to propane was 1:15, the growth time was 18 min, and the other parameters remained unchanged. In step 2, nickel oxide nanoparticles were used as the catalyst for carbon nanotube growth, and the loading method was impregnation, with a loading of approximately 0.4 mg / cm³. 2The secondary CVD temperature was 880 ℃, propane was used as the carbon source, the flow ratio of propane to hydrogen was 1:11, the flow ratio of ammonia to propane was 1:12, the growth was carried out at a constant temperature for 30 min, the etching solution concentration was 2.0 mol / L, the etching time was 20 h, and the other parameters remained unchanged. In step 3, melamine was used as the organic nitrogen source, and the nitrogen doping solution was prepared with anhydrous ethanol. The melamine concentration was 3.0 mg / mL, the impregnation time was 12 h, and the other parameters remained unchanged. In step 4, the calcination temperature is 580 ℃, and the calcination is carried out at a constant temperature for 2.5 h, while the other parameters remain unchanged; The remaining process steps and parameters are exactly the same as in Example 1, and the composite material is prepared and denoted as CoFe2O4-N-CNT / GF-3.

[0033] The composite material prepared in this embodiment uses in-situ nitrogen-doped three-dimensional graphene foam as the matrix framework, and nitrogen-doped carbon nanotubes are covalently grown in situ on the surface of the in-situ nitrogen-doped three-dimensional graphene foam framework to form a nitrogen-doped carbon nanotube modified graphene foam carrier. The surface of the nitrogen-doped carbon nanotube modified graphene foam carrier is in-situ coated with an organic nitrogen source-derived nitrogen-doped carbon layer, and CoFe2O4 bimetallic oxide nanoparticles are uniformly anchored in the organic nitrogen source-derived nitrogen-doped carbon layer to form a hierarchical integrated structure.

[0034] In this embodiment, the nitrogen-doped carbon nanotubes are mainly multi-walled carbon nanotubes with an average diameter of about 55 nm and an average length of about 18 μm. The in-situ nitrogen-doped three-dimensional graphene foam is a three-dimensional interconnected porous structure with pore sizes mainly distributed in the range of 110-330 μm, a porosity of about 98.9%, and a nitrogen element doping atomic percentage of about 1.0 at.

[0035] The CoFe2O4 bimetallic oxide nanoparticles have an average particle size of approximately 220 nm and are spatially confined and anchored by a nitrogen-doped carbon layer. The nitrogen-doped carbon layer derived from the organic nitrogen source has an average thickness of approximately 7 nm and a nitrogen element doping atomic percentage of approximately 2.5 at.%.

[0036] Comparative Example 1 This comparative example removes the in-situ growth modification step of carbon nanotubes; the remaining processes are completely consistent with Example 1, as detailed below: The operations of carbon nanotube growth catalyst loading and secondary CVD in-situ carbon nanotube growth in step 2 were deleted. The in-situ nitrogen-doped graphene foam supported by nickel foam prepared in step 1 was directly etched, cleaned and dried to obtain unmodified pure in-situ nitrogen-doped graphene foam support. The process parameters of subsequent bimetallic loading, nitrogen doping and calcination steps were exactly the same as in Example 1. A comparative composite material was prepared and denoted as CoFe2O4-N-GF.

[0037] The composite material prepared in this comparative example uses in-situ nitrogen-doped three-dimensional graphene foam as the matrix framework, and the surface of the framework is in-situ coated with a nitrogen-doped carbon layer derived from an organic nitrogen source, with CoFe2O4 bimetallic oxide nanoparticles anchored in the carbon layer.

[0038] In this comparative example, the in-situ nitrogen-doped three-dimensional graphene foam inherits the three-dimensional interconnected porous structure of nickel foam, with pore sizes mainly distributed in the range of 130-340 μm, a porosity of approximately 99.1%, and a nitrogen doping atomic percentage of approximately 1.1 at.

[0039] The average particle size of the CoFe2O4 bimetallic oxide nanoparticles is about 320 nm, and local aggregation occurs. The average thickness of the nitrogen-doped carbon layer derived from the organic nitrogen source is about 6 nm, and the nitrogen element doping atomic percentage is about 2.7 at.%.

[0040] Key process parameter screening experiment To verify the optimality and non-obviousness of the core process parameters of this invention, a series of screening experiments were carried out using the single-variable control method with Example 1 as the baseline group. Except for the variable parameters, the preparation process and test conditions of all control groups were completely consistent with those of Example 1.

[0041] 1. Screening of gas-phase nitrogen source flow rates in a single CVD process This experiment screened the flow ratio of ammonia to methane to verify the effect of the in-situ nitrogen doping ratio in the gas phase on the nitrogen content of the matrix and the catalytic performance. The experimental results are shown in Table 1 below.

[0042] Table 1

[0043] As the proportion of gaseous nitrogen source increases, the nitrogen doping content of the graphene foam matrix gradually increases. When the flow ratio is 1:10, the material achieves optimal bifunctional catalytic performance for both ORR and OER. When the nitrogen source proportion is too low, the number of doped nitrogen atoms is insufficient, resulting in a low density of highly active MNC sites and limited catalytic activity. Conversely, when the nitrogen source proportion is too high, excessive defects in the graphene framework lead to decreased matrix conductivity, which in turn worsens catalytic kinetics. This invention selects a flow ratio range of 1:5-1:20, with 1:10 as the optimal value. This optimal parameter range was obtained through systematic screening, achieving a balance between nitrogen doping amount and conductivity.

[0044] 2. Screening of catalysts for carbon nanotube growth This experiment screened the types of catalysts for carbon nanotube growth and verified the effects of different catalysts on the morphology and catalytic performance of carbon nanotubes. The experimental results are shown in Table 2 below.

[0045] Table 2

[0046] When iron(III) oxide (Fe3O4) is used as a catalyst, the grown carbon nanotubes exhibit the most uniform diameter and smallest size, resulting in the optimal catalytic performance of the material. This is because the Fe3O4 nanoparticles are gradually reduced to iron active sites during the CVD heating process, resulting in high nucleation density and uniform size. The grown carbon nanotubes have fewer defects, higher graphitization, and stronger covalent bonding with the graphene framework. In contrast, metal salt catalysts tend to aggregate at high temperatures, leading to a wider diameter distribution and decreased performance of the carbon nanotubes. This invention selects iron / cobalt / nickel-based catalysts as the possible options and Fe3O4 as the optimal solution, representing a creative choice based on comparative verification.

[0047] 3. Screening of secondary CVD growth temperatures This experiment screened the secondary CVD growth temperature of carbon nanotubes and verified the effect of temperature on the growth state and catalytic performance of carbon nanotubes. The experimental results are shown in Table 3 below.

[0048] Table 3

[0049] The material exhibits optimal overall catalytic performance at a growth temperature of 900 ℃. At excessively low temperatures, carbon source decomposition is incomplete, resulting in slow carbon nanotube growth, short lengths, limited increase in specific surface area, and insignificant toughening and loading site enhancement effects. Conversely, at excessively high temperatures, rapid carbon nanotube growth leads to entanglement and aggregation, blocking some porous channels and consequently reducing mass transfer efficiency. This invention selects a temperature range of 850-950 ℃, with 900 ℃ as the optimal value, achieving an optimal balance between carbon nanotube growth density, morphology, and mass transfer channels.

[0050] In summary, all the core process parameters of this invention were obtained through screening by multiple sets of parallel comparative experiments. The selection of each parameter range and the optimal value are not conventional techniques in this field. Furthermore, the simultaneous improvement of mechanical stability, nitrogen doping efficiency and bifunctional catalytic performance was achieved through parameter synergy, demonstrating significant inventiveness and technological progress.

[0051] Test Example 1 The bimetallic composite material based on graphene foam obtained in Example 1 was subjected to scanning electron microscopy (SEM). The SEM images are shown below. Figure 1 As shown.

[0052] like Figure 1 As shown, the material retains the complete three-dimensional interconnected porous network framework. Nitrogen-doped carbon nanotubes grow uniformly and vertically on the framework surface, forming a dense three-dimensional network structure without structural collapse or carbon nanotube aggregation. Under high magnification, CoFe2O4 nanoparticles are uniformly coated by the nitrogen-doped carbon layer and have good dispersion on the surface of carbon nanotubes and graphene foam framework, without obvious aggregation or shedding, confirming the successful construction of the hierarchical integrated structure designed in this invention.

[0053] The electrode materials prepared in Examples 1-3 and Comparative Example 1 were subjected to three-electrode testing, using a 0.1 mol / L KOH aqueous solution as the electrolyte, a platinum wire electrode as the counter electrode, and a saturated Ag / AgCl electrode as the reference electrode. Oxygen reduction reaction (ORR) test: High-purity oxygen was introduced into the electrolyte for 30 min until saturation before the test. The CV test voltage window was 0-1.2 V, and the scan rate was 100 mV / s. The LSV test voltage window was 0.2-1.1 V, the scan rate was 10 mV / s, and the test rotation speed was 400-2000 rpm. The number of electrons transferred was calculated using the Koutecky-Levich equation.

[0054] Oxygen Evolution Reaction (OER) Test: High-purity nitrogen gas was introduced into the electrolyte for 30 min before the test. The LSV test voltage window was 1.2-1.8 V, the scan rate was 10 mV / s, the rotation speed was 1600 rpm, and the value of 10 mA / cm² was calculated. 2 Overpotential at current density.

[0055] Table 4. Results of ORR electrocatalytic performance test

[0056] The results show that the ORR catalytic performance of the composite material prepared in this invention is significantly better than that of Comparative Example 1. Specifically, Example 1 exhibits an electron transfer number of 3.94, which is very close to the ideal 4-electron reaction system, demonstrating that its oxygen reduction reaction pathway is close to the optimal 4-electron transfer process and exhibits excellent catalytic kinetics. The onset potential of Example 1 (0.89 V) and half-wave potential (0.82 V) are 100 mV and 120 mV higher than those of Comparative Example 1, respectively, with a 39.6% increase in limiting current density and a 23.1% increase in electron transfer number.

[0057] Comparative Example 1, lacking nitrogen-doped carbon nanotube modification, had a limited specific surface area of ​​the support, leading to the easy aggregation of CoFe2O4 active particles and insufficient exposure of effective catalytic active sites. Furthermore, the absence of in-situ nitrogen doping with carbon nanotubes resulted in a low overall nitrogen doping content and a limited number of highly active Co / Fe-NC sites, thus significantly reducing both ORR catalytic activity and reaction kinetics. These results demonstrate that the present invention, through a combination of bimetallic synergy, tertiary nitrogen doping, and carbon nanotube toughening, significantly enhances ORR catalytic activity.

[0058] Table 5. OER Electrocatalytic Performance Test Results

[0059] The results show that the OER catalytic performance of the composite material prepared in this invention is significantly better than that of Comparative Example 1. Specifically, Example 1 exhibits significantly better OER catalytic performance at 10 mA / cm².2 The overpotential at the current density is only 350 mV, and the Tafel slope is as low as 75 mV / dec, which is 170 mV lower than the 520 mV overpotential of Comparative Example 1 and the Tafel slope is reduced by 40%, proving that its oxygen evolution reaction kinetics are fast and its catalytic efficiency is high.

[0060] In Comparative Example 1, the three-dimensional continuous conductive network without carbon nanotubes exhibits high charge transfer resistance within the electrode. Furthermore, the agglomeration of active particles reduces the interfacial catalytic contact area, raising the reaction energy barrier and resulting in a significant decline in OER catalytic performance. Combined with ORR test results, it is evident that the hierarchical integrated structure of this invention can simultaneously optimize the reaction pathways and kinetics of both oxygen reduction and oxygen evolution reactions, achieving a synchronous improvement in both ORR and OER bifunctional catalytic performance.

[0061] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a composite material based on graphene foam, characterized in that, Includes the following steps: (1) Using chemical vapor deposition, with nickel foam as a template, carbon source and gas nitrogen source are introduced, and in-situ nitrogen-doped three-dimensional graphene foam is grown on the surface of nickel foam through a one-time chemical vapor deposition CVD combined with gas phase in-situ nitrogen doping process, thus obtaining in-situ nitrogen-doped three-dimensional graphene foam loaded with nickel foam. (2) Carbon nanotube growth catalyst is loaded on the surface of the in-situ nitrogen-doped three-dimensional graphene foam supported by nickel foam obtained in step (1). The nitrogen-doped carbon nanotubes are covalently grown on the surface of the in-situ nitrogen-doped three-dimensional graphene foam skeleton supported by nickel foam by a secondary chemical vapor deposition method combined with the gas phase in-situ nitrogen doping process. After etching to remove the nickel foam template, the graphene foam carrier modified with nitrogen-doped carbon nanotubes is obtained. (3) The CoFe2O4 bimetallic oxide nanoparticle dispersion was loaded onto the surface of the nitrogen-doped carbon nanotube modified graphene foam carrier obtained in step (2), dried, and then impregnated in an organic nitrogen source doping solution. The precursor was obtained by in-situ polymerization at room temperature. (4) The precursor obtained in step (3) is calcined in an inert atmosphere to obtain the composite material based on graphene foam.

2. The method for preparing the composite material based on graphene foam according to claim 1, characterized in that, In step (1), the specific steps of chemical vapor deposition are as follows: The nickel foam was placed in a CVD tube furnace and heated to 960-990℃ at a heating rate of 8-12℃ / min under argon protection. Hydrogen was then introduced and reduced at a constant temperature for 25-40 min at a flow rate of 20-60 sccm. Then a mixture of carbon source, hydrogen and gaseous nitrogen source was introduced, with a flow rate ratio of carbon source to hydrogen of 1:(12-18) and a flow rate ratio of gaseous nitrogen source to carbon source of 1:(5-20), and the mixture was grown at a constant temperature for 12-18 min. After growth, the temperature was lowered to room temperature under a protective atmosphere of mixed argon and hydrogen to obtain in-situ nitrogen-doped three-dimensional graphene foam supported on nickel foam.

3. The method for preparing the composite material based on graphene foam according to claim 1 or 2, characterized in that, In step (2), the carbon nanotube growth catalyst is one or more of iron salts, cobalt salts, nickel salts, iron oxide, cobalt oxide, iron(II,III) oxide, or nickel oxide, and the loading method is impregnation, spin coating, or sputtering, with a catalyst loading of 0.1-0.5 mg / cm³. 2 ; The specific steps of the secondary CVD combined with gas phase in-situ nitrogen doping process are as follows: under argon protection, the temperature is raised to 850-950 ℃, and a mixed gas of carbon source, hydrogen and gas phase nitrogen source is introduced. The flow ratio of carbon source to hydrogen is 1:(10-15), and the flow ratio of gas phase nitrogen source to carbon source is 1:(3-15). The growth is carried out at a constant temperature for 15-30 min. The etching was performed using a 1.0-2.5 mol / L FeCl3 / HCl mixed etching solution for 18-30 h. The carbon source is one or more of methane, ethylene, propylene, ethane, or propane; the gaseous nitrogen source is one or more of ammonia, urea vapor, or melamine vapor.

4. The method for preparing the composite material based on graphene foam according to claim 1, characterized in that, In step (3), the concentration of the CoFe2O4 bimetallic oxide nanoparticle dispersion is 0.8-4.5 mg / mL, the loading method is impregnation, the impregnation time is 2-4 h, and the impregnation and drying are repeated 2-4 times; the solute of the organic nitrogen source doping solution is one or more of dopamine hydrochloride, dopamine, melamine, pyrrole, aniline, urea or chitosan, the concentration of organic nitrogen source in the organic nitrogen source doping solution is 1.2-4.8 mg / mL, the impregnation polymerization reaction time is 8-14 h, and the reaction environment is room temperature and protected from light.

5. The method for preparing the composite material based on graphene foam according to claim 1, characterized in that, In step (4), the calcination process is as follows: under a high-purity nitrogen or argon atmosphere, the temperature is raised to 580-630 ℃ at a heating rate of 3-6 ℃ / min, and calcined at a constant temperature for 1.5-2.5 h. After calcination, the temperature is lowered to room temperature under an inert atmosphere.

6. A graphene foam-based composite material prepared by the preparation method according to any one of claims 1-5, characterized in that, The composite material uses in-situ nitrogen-doped three-dimensional graphene foam as the matrix framework, and nitrogen-doped carbon nanotubes are covalently grown in situ on the surface of the in-situ nitrogen-doped three-dimensional graphene foam framework to form a nitrogen-doped carbon nanotube modified graphene foam carrier. The surface of the nitrogen-doped carbon nanotube modified graphene foam carrier is in-situ coated with a nitrogen-doped carbon layer derived from an organic nitrogen source. CoFe2O4 bimetallic oxide nanoparticles are uniformly anchored in the nitrogen-doped carbon layer derived from the organic nitrogen source, forming a hierarchical integrated structure.

7. The graphene foam-based composite material according to claim 6, characterized in that, The nitrogen-doped carbon nanotubes are single-walled or multi-walled carbon nanotubes with a diameter of 10-100 nm and a length of 5-50 μm; the in-situ nitrogen-doped three-dimensional graphene foam is a three-dimensional interconnected porous structure with a pore size of 80-350 μm, a porosity of 98.5%-99.5%, and a nitrogen doping atomic percentage of 0.5-2.0 at.

8. The graphene foam-based composite material according to claim 6, characterized in that, The CoFe2O4 bimetallic oxide nanoparticles have a particle size of 80-450 nm and are spatially confined and anchored by a nitrogen-doped carbon layer. The thickness of the nitrogen-doped carbon layer derived from the organic nitrogen source is 2-12 nm, and the percentage of nitrogen doping atoms is 1.2-4.5 at.

9. The composite material based on graphene foam according to claim 6, characterized in that, The organic nitrogen source is one or more of dopamine hydrochloride, dopamine, melamine, pyrrole, aniline, urea, or chitosan.